EMPATHY AND COMPASSION: THE PLACE OF MEMORY - Sarmento-Pantoja, Tânia Maria (2023)
From the humanitarian crisis in Syria to its representation through the photograph of the little Aylan Kurdi – a Syrian boy of Kurdish ethnicity, found dead on a beach in Turkey – we think in this article the testimony through the aesthetics of the image and its impact in denouncing barbarism, as well as the human challenge of connecting with others in building lasting bonds through dialogue based on empathetic interaction and in tune with reparation. From the levinasian perspective of an ethics of responsibility, in a world connected to the internet, we understand how empathic sensitivity, when in the domain of the image, creates a relationship of similarity with the other, and even creates conditions to think like the other and about the other. another, either to succeed in mediating conflicts, or to reflect on the use of photography (also) as a place of memory.